Love's unending legacy - Levinson, Larry; Halmi, Robert, 1957-; Griffiths, Mark; Wallace, Pamela; Cottrell, Erin; Midkiff, Dale, 1959-; Nash, Stephanie; Florek, Dave; Coleman, Holliston; Browne, Victor; Kiner, Kevin; Oke, Janette, 1935-; et al. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2007)
Two years after the death of her husband, Missie knows that it is time to move on. She heads home with her son to be near her parents and to return to teaching. Certain she will never find love again, Missie redirects her feelings and when the "orphan train" arrives in town, she adopts Belinda, a feisty young teenager who's arrived with a secret. As Missie struggles with raising Belinda, she finds she is falling for the local sheriff who might be the only man who can help her save Belinda... and herself.
Originally broadcast as a motion picture on television in 2007.
Closed captioned for the hearing impaired.
Based on the novel in the "Love comes softly" series by Janette Oke.
Director of photography, Brian Shanley ; editor, Colleen Halsey ; music, Kevin Kiner.
Erin Cottrell, Dale Midkiff, Stephanie Nash, Dave Florek, Holliston Coleman, Victor Browne.
MPAA rating: Not rated.
Keywords: Widows -- Drama; Older child adoption -- Drama; Single mothers -- Drama; Women pioneers -- Drama; Sheriffs -- Drama; Grandparents -- Drama; Frontier and pioneer life -- Drama; Feature films; Made-for-TV movies; Films for the hearing impaired